Bone mineral density in adolescent female athletes: relationship to exercise type and muscle strength - Duncan, C. S.; Blimkie, C. J.; Cowell, C. T.; Burke, S. T.; Briody, J. N.; Howman-Giles, R. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: This study investigated the influence of different exercise types and differences in anatomical distribution of mechanical loading patterns on bone mineral density (BMD) in elite female cyclists, runners, swimmers, triathletes, and controls (N = 15 per group). Associations between leg strength and BMD were also examined. METHODS: Areal BMD (g.cm[minus sign]2) was assessed by duel-energy x-ray absorptiometry (DXA) (total body (TB), lumbar spine (LS), femoral neck (FN), legs, and arms). Right knee flexion and extension strength was measured using a Cybex Norm isokinetic dynamometer at 60esponses were seen in patients previously treated with anthracyclines (75%) (95% CI 57-92), and in patients who had had no prior chemotherapy (90%) (95% CI 71-100). Responses were seen in all metastatic sites: liver 80%, lung 76%, bone 69%, and soft tissue.s[minus sign]1. RESULTS: Runners had significantly higher unadjusted TB, LS, FN, and leg BMD than controls (P < 0.05); higher TB, FN, and leg BMD than swimmers (P < 0.05); and greater leg BMD than cyclists (P < 0.05). Absolute knee extension strength was significantly (P < 0.01) correlated (0.33 [less-than-or-equal] r [less-than-or-equal] 0.44) with TB, FN, LS, and leg BMD for all groups combined. Weaker but still significant correlations (0.28 [less-than-or-equal] r [less-than-or-equal] 0.33) existed for normalized (per leg lean tissue mass) knee extension strength and all BMD sites, except FN BMD. There were no significant correlations between absolute or normalized knee flexion strength and any of the BMD variables. Absolute knee extension strength was entered as the second independent predictor for LS and leg BMD in stepwise multiple linear regression analysis (MLRA), accounting for increments of 4% and 12%, respectively, in total explained variation. CONCLUSION: We conclude that running, a weight bearing exercise, is associated with larger site-specific BMD than swimming or cycling, that the generalized anatomical distribution of loads in triathlon appears not to significantly enhance total body BMD status, and that knee extension strength is only a weak correlate and independent predictor of BMD in adolescent females.